Actual usage conditions and energy consumption of refrigerator-freezers - Saidur, Rahman; Masjuki, Haji Hassan; Eow, K.F.; Jamaluddin, M.Y. (International Energy Journal, 2006)
About 19 of the total electricity production is consumed in the residential sector and this fraction is expected to grow in future. Air conditioners, refrigerators, washing machines and other appliances are significant energy users in this sector. In this paper, the energy consumption and internal cabinet temperatures of 30 domestic refrigerators have been monitored to give an overview of the usage pattern of this appliance in Malaysian households. A questionnaire was designed to get relevant information regarding the usage of this appliance in the actual kitchen environment as well. This information is paramount in shaping or implementing a program that would get more support from users. The statistical analysis such as clustering and segmentation were manipulated and utilized in order to show the influence of the usage conditions on the temperature. The paper also calculated energy, bill savings and associated emission reductions by replacing an old inefficient refrigerator with a new efficient one.